Arctic: why India should pursue the North Pole from a science and technology perspective? - Nayak, Shailesh; Suba Chandran, D (CURRENT SCIENCE ASSOCIATION, 2020)
The Arctic has been receiving a lot of attention recently due to environmental and economic reasons. The continuing reduction of sea ice and sheet ice is likely to affect global climate significantly. It is expected that these changes will affect monsoon as well as inundate our coasts. India has a modest presence in the Arctic, mainly for scientific purposes. The changing Arctic is likely to offer many economic opportunities, especially for ensuring energy security and access to rare earths. India needs to enhance its presence for launching scientific projects to study the interactions between cryosphere, atmosphere and ocean in order to understand long-term impacts on the country. It is essential that India defines its strategy as well as a policy for the Arctic in the near future and contributes towards generating strategic knowledge for the region. Such knowledge will help ensure food, energy and resource security for the country.